Lidia's from our family's table to yours : more than 100 recipes made with love for all occasions - Bastianich, Lidia; Manuali, Tanya Bastianich (Alfred A. Knopf, 2023)
"Nothing brings a family together like food. And no one knows food like Lidia Bastianich. In this inviting, deeply personal new cookbook, she shares, for the first time, the dishes she cooks for those she loves the most. This is the first book Lidia has written since her beloved - not just by Lidia's family but by millions of book and TV fans - mother died. With all the family stories and recipes, in some ways this book can be seen as a tribute to Nona. Here are the traditional recipes that graced Lidia's table as a young girl-Prosciutto and Onion Frittata, Rigatoni with Sausage and Cabbage-alongside the new creations-Sweet Potato Chickpea Gnocchi with Gorgonzola, Cheesy Baked Chicken Wings-she makes for her children and grandchildren today. Bringing together more than a hundred delicious, flavorful, and easy-to-make Italian recipes, From Our Family's Table to Yours is a celebration of the dishes Lidia's family turn to over and over-and yours will, too. From Crespelle with Herb Pesto to Penne with Sausage, Mushrooms and Ricotta Vegetable Polpette to Mimosa Cake, this book is the next-best thing to a seat at Lidia's kitchen table"--